Purification of Candida guilliermondii and Pichia ohmeri killer toxin as an active agent against Penicillium expansum - Coelho, Alexandre Rodrigo; Tachi, Masahico; Pagnocca, Fernando Carlos [UNESP]; Andrade Nobrega, Gisele Maria; Hoffmann, Fernando Leite [UNESP]; Harada, Ken-ichi; Hirooka, Elisa Yoko (Taylor & Francis Ltd, 2009)
An antifungal assay with cell-free culture supernatant of Pichia ohmeri 158 and Candida guilliermondii P3 was tested against Penicillium expansum strain #2 at 25C by measuring hyphal length and percentage conidia germination. C. guilliermondii was more effective against P. expansum conidia germination (58.15% inhibition), while P. ohmeri showed higher inhibition of mycelial growth (66.17%), indicating a probable mechanism associated with killer activity. This killer toxin (molecular mass 3 kDa) was partially purified by normal phase HPLC, using TSKgel Amide-80 analytical and preparative columns. Compared with crude extract, the killer toxin eluted from the post analytical column significantly inhibited P. expansum:% inhibition rose from 42.16 to 90.93% (C. guilliermondii) and 39.32 to 91.12% (P. ohmeri) (p 0.05). The one-step purification process was adequate in isolating killer toxin from culture supernatant and also increased anti-Penicillium activity.
Keywords: Penicillium expansum; antagonist yeasts; killer toxin; Biological control